PENYULUHAN TENTANG OBAT TRADISIONAL TERHADAP PENYAKIT ASAM URAT DI SMK SWASTA YAPIM BIRU-BIRU - Sulasmi, Sulasmi Sulasmi (INSTITUT KESEHATAN DELI HUSADA, 2023)
Pain in the joint area is common condition that occurs in gout sufferers. Pain in the joint area occurs because the uric acid level in the blood is too high. High levels of uric acid will cause a buildup of crystals in the joint area. If gout sufferers take analgesic drugs continuously, undesirable effects can occur. So gout sufferers need treatment without drugs to treat it. A non-drug treatment to relieve pain in the joint area and reduce uric acid levels is a concoction of soursop leaves. Soursop leaves contain the natural antioxidant acetogenin and several phenolics, which work by inhibiting the action of xhantin oxidase which is responsible for converting hypoxhantin into xhantin. The aim of this community service is to provide information to the public about the benefits of soursop leaves as a traditional medicinal ingredient in treating gout. The implementation of this PKM activity was carried out at the Yapim Biru-biru Private Vocational School, which is a vocational high school located in Delitua, North Sumatra, Indonesia. Next, students had their level of knowledge measured by being given a quiz and the results showed that 9 out of 10 questions students were able to understand the benefits of soursop leaves as a non-drug treatment for gout.